Accessing the Impact Mechanism of Sense of Virtual Community on User Engagement - Zhao, Hong; Shi, Qiaohong (Frontiers in Psychology, 2022)
Although research has begun to explore the influence patterns of sense of virtual community, there is limited research on how sense of virtual community affects educational virtual community user engagement. Based on the educational virtual community context, this study constructs a theoretical model with moderation and mediation to explore the mediation mechanism of sense of virtual community affecting user engagement and its boundary conditions. In this study, the data collected from 377 users are analyzed by structural equation modeling. The research findings found that not only effective commitment has a mediating role between sense of virtual community and user engagement, but also perceived support has a moderating role in the process of effective commitment's influence on user engagement. This study examines the practical effects of sense of virtual community in the context of educational virtual community use and reveals the mechanism of the effect of sense of virtual community on user engagement.